The Use of Learning Media-Based Augmented Reality (AR) to Improving Integrated Science and Social Studies Literacy - Tetep, Tetep; Ismail, Ali; Nasrulloh, Iman (Jurnal Pendidikan Progresif, 2023)
The use of Learning Media-Based Augmented Reality (AR) to Improving Integrated Science And Social Studies Literacy. This study aimed to explore the use of learning media-based Augmented Reality to enhance integrated science and social studies literacy in primary school. AR-based learning media was integrated into the IPAS subject. The participants in this study were 48 fifth-grade students from elementary schools, divided into experimental (24 students) and control groups (24 students). Each class employed a cooperative learning approach, with students in the experimental groups engaged in using AR-based learning media to support their learning process. The research method used was non-equivalent pretest-posttest design. The instruments used to test literacy skills (both pretest and posttest) consisted of 5 items. The results indicate a significant difference in the enhancement of students’ literacy skills in the experimental groups compared to the control group. This suggests that the use of the AR-based learning approach enhanced students’ literacy skills in the context of the IPAS subject. Keywords: ar learning media, ipas learning, science literacy, social studies literacy.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202328